2016
DOI: 10.1103/physrevaccelbeams.19.081303
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of positrons generation based on laser wakefield electron acceleration

Abstract: Laser based positron represents a new particle source with short pulse duration and high charge density. Positron production based on laser wakefield electron acceleration (LWFA) has been investigated theoretically in this paper. Analytical expressions for positron spectra and yield have been obtained through a combination of LWFA and cascade shower theories. The maximum positron yield and corresponding converter thickness have been optimized as a function of driven laser power. Under the optimal condition, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…A positron beam was generated from the interaction of the electron beam with a secondary Pb converter of variable thickness. The maximum measured positron yield was ∼ 1 × 10 8 e + /shot, obtained from a converter thickness of d = 1 cm, which corresponds to a thickness of two radiation lengths (L Pb rad ≃ 0.5 cm), as expected for the Bethe-Heitler process, and confirmed numerically and theoretically by Wu et al [103].…”
Section: Referencessupporting
confidence: 78%
See 1 more Smart Citation
“…A positron beam was generated from the interaction of the electron beam with a secondary Pb converter of variable thickness. The maximum measured positron yield was ∼ 1 × 10 8 e + /shot, obtained from a converter thickness of d = 1 cm, which corresponds to a thickness of two radiation lengths (L Pb rad ≃ 0.5 cm), as expected for the Bethe-Heitler process, and confirmed numerically and theoretically by Wu et al [103].…”
Section: Referencessupporting
confidence: 78%
“…Despite the large positron yield and properties of those beams, interesting for applications in material science, their properties need further improvement before being used in fields such as high energy physics and colliders. For this reason, the properties of positron beams expected from the upcoming multi-PW laser facilities have been numerically studied [102,103]. Considering the multi-GeV electron beams expected from these facilities, Alejo et al have shown that ultra-short positron beams can be used as injector for a future multi-stage, plasma-based positron accelerator [102] (see Table 1).…”
Section: Prospectsmentioning
confidence: 99%
“…Development of laser-matter interactions and ensuing new phenomena, have resulted in more extensive research in this field, and the research on the laser-matter interaction is more and more extensive. The coupling between QED process and plasma dynamics in QED plasma produced by relativistic ultra-intense laser is a nonlinear and complex process, for example, the generation of ultra-intense γ-rays, and high energy dense electron-positron pairs [28][29][30][31][32][33][34][35]. Numerical simulation is an important method describing such interactions.…”
Section: Introductionmentioning
confidence: 99%